Effect of Time, Inoculum size (%) and Mass Substrate on succinic acid production from glycerol residue using immobilized Escherichia Coli - Nik Nor Aziati, Abdul Aziz; Mimi Sakinah, A. M. (AENSI Publishing, 2016)
The study on succinic acid production from glycerol residue using immobilized Escherichia coli in a simple fermentation process has shown a potentially low-cost production process. In this research, the bacterial cells were prepared by the entrapment method. This method was chosen since it was reported to be an effective method for large scale production of succinic acid. The effects of different times, inoculum size, and mass substrate values on succinic acid production were studied. Batch culture technique was employed to grow the Escherichia coli and the entrapment method for the immobilization of the cells. The optimum condition was observed as 30 g mass substrate (117.99 g/L succinic acid production), inoculum size 20 % working volume (102.30 g/L succinic acid production),and time of 4 h (110.20 g/L succinic acid production). This process condition gave the maximum succinic acid concentration. Preliminary characterization of the raw material was done by using the High-Performance Liquid Chromatography and Fourier Transform Infrared Spectrometry (FTIR). The results were then compared to the raw material (glycerol residue), pretreated glycerol (after pretreatment) and succinic acid concentrations. The effects of mass substrate, inoculums densities, and time were significant on the succinic acid production by immobilized cells.